Clinical malaria in the tropics. - White, N; Pukrittayakamee, S (1993)
Although malaria has been largely eradicated from temperate countries, it is on the increase in the tropics. Infection with Plasmodium falciparum affects a vast number of people and kills over a million annually. Severe malaria is a multisystem disease affecting particularly the central nervous system (causing coma and convulsions), the kidneys (resulting in acute tubular necrosis), and the liver (contributing to lactic acidosis and hypoglycaemia). Acute pulmonary oedema (acute respiratory distress syndrome) may occur in adults particularly in association with renal impairment. In children these symptoms are rare, whereas hypoglycaemia, lactic acidosis and severe anaemia are more common. Malaria should be suspected in any febrile patient living in or returning from the tropics, and a blood smear examined. Chloroquine has been the mainstay of antimalarial treatment for the past 40 years, but resistance in P. falciparum is now widespread throughout the tropics and has recently been recognised in P. vivax from Oceania. Sulfadoxine-pyrimethamine resistance is also common. Fortunately, quinine, and the newly introduced compounds, halofantrine and mefloquine, can be relied upon nearly everywhere. The most rapidly acting and effective of all antimalarial drugs, artemisinin and its derivatives, have come from China. They offer a genuine prospect of reducing mortality from malaria in the tropics.